Calcified Chondroid Mesenchymal Neoplasm: Exploring the Morphologic and Clinical Features of an Emergent Entity With a Series of 33 Cases - Kallen, Michael E; Michal, Michael; Meyer, Anders; Suster, David I; Olson, Nicholas J; Charville, Gregory W; Perret, Raul; Gross, John M (The American journal of surgical pathology, 2023)
Calcified chondroid mesenchymal neoplasm is a term proposed for tumors with a spectrum of morphologic features, including cartilage/chondroid matrix formation, that frequently harbor FN1 gene fusions. We report a series of 33 cases of putative calcified chondroid mesenchymal neoplasms, mostly referred for expert consultation out of concern for malignancy. Patients included 17 males and 16 females, with a mean age of 51.3 years. Anatomic locations include the hands and fingers, feet and toes, head and neck, and temporomandibular joint; 1 patient presented with multifocal disease. Radiologic review showed soft tissue masses with variable internal calcification, which occasionally scalloped bone but in all cases appeared indolent/benign. Tumors had a mean gross size of 2.1 cm and a homogenous rubbery to fibrous/gritty tan-white cut surface. Histology demonstrated multinodular architecture with a prominent chondroid matrix and increased cellularity towards the periphery of the nodules. The tumor cells were polygonal with eccentric nuclei and bland cytologic features and showed a variable amount of increased spindled / fibroblastic forms in the perinodular septa. The majority of cases had notable grungy and/or lacy calcifications. A subset of cases demonstrated at least focal areas of increased cellularity and osteoclast-like giant cells. Herein, we confirm the distinct morphologic and clinicopathologic features associated with this entity with the largest series to date, with a focus on practical diagnostic separation from similar chondroid neoplasms. Awareness of these features is critical in avoiding pitfalls, including a malignant diagnosis of chondrosarcoma.
Keywords: Toes; nádory z pojivové a měkké tkáně; nádory kostí; Chondrosarcoma; chondrosarkom; prsty nohy; Male; Cartilage; lidé; Female; mužské pohlaví; ženské pohlaví; Bone Neoplasms; lidé středního věku; Humans; chrupavka; Middle Aged; Neoplasms, Connective and Soft Tissue